SECURING OF ECONOMIC EQUILIBRIUM AND ECOLOGIC BALANCE - Maslovska, Lyudmyla (Journal of European Economy, 2002)
The article, from the viewpoint of modern economic studies, argues that economic development and economic equilibrium are increasingly more determined by limitations of natural resources and ecology issues. Current complicated ecologic situation, decreasing productivity of geo-ecosystems, depletion of natural resources, and reducing bio-diversity are interpreted as non-equilibrium of living environment and of productive activity of a society, or as the threat to ecology. Special attention is drawn to interconnection and interrelation between stable ecology-friendly development and development in economy. The economic development in author’s opinion brings about new quality of productive forces, leads to changes in production relationships, and renews factors of production and vital functions by reducing consumption of natural resources. Development based on non-traditional factors, such as innovative technological, institutional and nature-efficient, is defined in the article as biosphere-compatible and able to ensure equilibrium and security in a wide scope - economic, social, and ecological.